Transcutaneous auricular vagus stimulation (taVNS) improves human working memory performance under sleep deprivation stress - Zhao, Rui; Chang, Meng-Ying; Cheng, Chen; Tian, Qian-Qian; Yang, Xue-Juan; Du, Meng-Yu; Cui, Ya-Peng; He, Zhao-Yang; Wang, Fu-Min; Kong, Yao; Deng, Hui; Lu, Li-Ming; et al. (Behavioural brain research, 2023)
Many human activities require high cognitive performance over long periods, while impairments induced by sleep deprivation influence various aspects of cognitive abilities, including working memory (WM), attention, and processing speed. Based on previous research, vagal nerve stimulation can modulate cognitive abilities, attention, and arousal. Two experiments were conducted to assess the efficacy of transcutaneous auricular vagus nerve stimulation (taVNS) to relieve the deleterious effects of sleep deprivation. In the first experiment, 35 participants completed N-back tasks at 8:00 a.m. for two consecutive days in a within-subject study. Then, the participants received either taVNS or earlobe stimulation (active control) intervention in two sessions at random orders after 24 h of sustained wakefulness. Then, they completed the N-back tasks again. In the second experiment, 30 participants completed the psychomotor vigilance task (PVT), and 32 completed the N-back tasks at 8:00 a.m. on the first and second days. Then, they received either taVNS or earlobe stimulation at random orders and finished the N-back and PVT tasks immediately after one hour. In Experiment 1, taVNS could significantly improve the accuracy rate of participants in spatial 3-back tasks compared to active control, which was consistent with experiment 2. However, taVNS did not specifically enhance PVT performance. Therefore, taVNS could be a powerful intervention for acute sleep deprivation as it can improve performance on high cognitive load tasks and is easy to administer. •Working memory and alertness were impaired stably after 24-hour sleep deprivation.•taVNS improved working memory performance accuracy after 24-hour sleep deprivation.•taVNS showed large potential to be a fatigue countermeasure after sleep deprivation.